DFT studies on PbO2 and binary PbO2/SnO2 thin films - Fabris, G. S.L.; Azevedo, D. H.M. [UNESP]; Alves, A. C. [UNESP]; Paskocimas, C. A.; Sambrano, J. R. [UNESP]; Cordeiro, J. M.M. [UNESP] (Elsevier, 2022)
Periodic quantum mechanics DFT calculations have been employed to investigate surface and electronic properties of β-PbO2 thin films and binary β-PbO2/SnO2 thin films with crystallographic planes (001), (010), (101), and (110) in both cases. The results show significant increases in the band gap energy of the pure PbO2 films compared to that of the bulk, due to a marked increase in the minimum energy of the conduction band. The relative surface stability follows the sequence (110) > (101) > (010) > (001). The surfaces become more unstable, and with a more accentuated ionic character after coating with SnO2, however, the relative stability of the surfaces does not change. Thus, the preferential growth direction and the crystalline shape of the coated films are maintained. The SnO2 coating causes significant changes in the band gap, with increases in the films with (001) and (010) surfaces, while a decrease is noticed in the band gap energy of the films with (110) and (101) surfaces.
Keywords: Binary films; DFT; PbO2; Semiconductors; SnO2; Surface stability